Analisis Proses Manajemen Risiko Teknologi Informasi Sistem Infrastruktur Telekomunikasi (InfraTel) PT. Telkom Indonesia menggunakan Framework ISO 31000:2009 - Nazruddin Safaat H (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Telecommunications Infrastructure is a very important for PT. Telkom Indonesia, because asTelecommunications company, Telkom’s services and products can not be separated from the use of theTelecommunications Infrastructure. Besides it is important for the company, Telkom’sTelecommunicationsInfrastructure often impaired the events that occurred in Indonesiasuch as natural disasters (floods,lightning, hurricanes, earthquakes, tsunamis), the incidence of fires and other events. ThereforeTelkom'sTelecommunication Infrastructure risk management is very important to achievement of the goals of thecompany.This research examines IT risk management based on ISO 31000 with a case study Telkom'sTelecommunications Infrastructure.The research methodology used "Case Study Research: Design andMethods" consisting of 6 (six) stages of the research, that are literature review, data collection, dataanalysis, design risk management framework, risk management processing and reporting.Researchfocused on the implementation risk management processes of Telkom's Telecommunication Infrastructure.Risk identification process using the approach method of Failure Mode and Effect Analysis (FMEA), Riskanalysis using the methods of causal analysis and the methods to be used in risk evaluation is aqualitative method of risk ranking schemes.Based on the results of risk assessment (identification, analysisand risk evaluation) will be determined the appropriate risk treatment for the problem of system failureTelkom’s Telecommunications Infrastructure.Keywords :Telecommunications Infrastructure, Information Technology Risk Management, FMEA, ISO31000.